The importance of open emergency surgery in the treatment of acute mesenteric ischemia. Issue 1 (December 2015) - Duran, Mansur; Pohl, E.; Grabitz, K.; Schelzig, H.; Sagban, T.; Simon, F.
Abstract Objective Acute mesenteric ischemia (AMI) is a complex disease with a high mortality rate. A patient's chance of survival depends on early diagnosis and rapid revascularization to prevent progression of intestinal gangrene. We reviewed our experience with open surgery treatment in 54 cases of AMI. Methods A monocentric retrospective study was conducted between 01/01/2001 and 04/30/2014; 54 AMI patients with a mean age of 56.6 years underwent surgery (26 women and 28 men). Retrospectively, the risk factors, management until diagnosis, vascular therapy and follow-up were evaluated. Results The symptom upon admission was an acute abdominal pain event. The delay time from admission to surgery was, on average, 13.9 h (n  = 34). The therapeutic procedures were open surgical operations. The complication rate was (53.7 %) (n  = 29). The 30-day mortality was 29.6 % (n  = 16). The late mortality rate was 24.1 % (n  = 13), and the cumulative survival risk was 44.6 %. Survival was, on average, 60.54 months; however, in the over 70-year-old patient subgroup, the survival rate was 9.5 months (p  = 0.035). The mortality rate was 27 % (n  = 22) in the <12 h delay group, 20 % (n  = 5) in the 12–24 h delay group, and 50 % (n  = 7) in the > 24 h delay group. Conclusions The form of therapy depends on the intraoperative findings and the type of occlusion. Although the mortality rate has decreased in the last decade, in patients over 70 years of age, a significantly worse prognosis was seen.